2008
DOI: 10.1063/1.2939121
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of nitroxide hyperfine coupling constants in solution from combined nanosecond scale simulations and quantum computations

Abstract: We present a combined theoretical approach based on analyzing molecular dynamics trajectories (at the nanosecond scale) generated by use of classical polarizable force fields and on quantum calculations to compute averaged hyperfine coupling constants. That method is used to estimate the constant of a prototypical nitroxide: the dimethylnitroxide. The molecule is embedded during the simulations in a cubic box containing about 500 water molecules and the molecular dynamics is generated using periodic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
69
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 45 publications
4
69
0
1
Order By: Relevance
“…In a recent study, we have addressed the three above points by investigating the properties of the solvated dimethylnitroxide (CH 3 ) 2 NO radical [25]. In particular, we demonstrated that it is possible to accurately reproduce the (CH 3 ) 2 NO a N value (within about 2%) with the following strategy:…”
Section: Introductionmentioning
confidence: 95%
“…In a recent study, we have addressed the three above points by investigating the properties of the solvated dimethylnitroxide (CH 3 ) 2 NO radical [25]. In particular, we demonstrated that it is possible to accurately reproduce the (CH 3 ) 2 NO a N value (within about 2%) with the following strategy:…”
Section: Introductionmentioning
confidence: 95%
“…The molecular properties of these nitroxides strongly depend on the chemical environment, and recent theoretical simulations have achieved a detailed characterization of such dependencies for isotropic solutions in non-polar/ polar and protic/aprotic solvents [18][19][20][21][22]. Besides the effects of complex chemical environment, ESR parameters are also affected by intra-molecular dynamics.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we proposed such a protocol to compute hyperfine coupling constants (hcc's) of flexible nitroxides in water [1,2]. It is based on combining nanosecond-scale classical molecular dynamics (MD) with large-scale QM/MM computations on small nitroxide/ water clusters extracted along the MD trajectories.…”
Section: Introductionmentioning
confidence: 99%